Needle breakage as an unusual complication of intravenous therapy: a case report - Liu, YanQun; Xu, HeXing; Fang, LongYun; Wen, Ji; Cui, HuZhe; Qin, XiangZheng (Journal of the Pakistan Medical Association, 2024)
Residual intravenous foreign bodies following hand trauma are relatively rare; only a few previous reports of this situation are available. It has been reported that foreign bodies often migrate to the heart and atrium dextrum. Herein, we report a recent case of needle breakage in the dorsal vein of the hand that was removed with lignification using an intraoperative C-arm fluoroscopy machine and tape tourniquet to avoid proximal movement during removal. The mandate should be to remove within the capacity allowed so that rare cases and terrible complications can be avoided. The case was seen at The Yanji City, Jilin Province, China at the Yanbian University Hospital emergency at February 20, 2023. Keywords: Complications, Needle breakage, Foreign body, Intravenous therapy, Case report.